Жовчносекреторна функція печінки самок щурів в умовах блокади естрогенових рецепторів тамоксифеном - Боровець, Оксана; Макарчук, Микола; Весельський, Станіслав; Решетнік, Євдокія; Бенедь, Володимир; Borovets, Oksana; Makarchuk, Mykola; Veselsky, Stanislav; Reshetnik, Evdokiay; Bened’, Volodymyr (Східноєвропейський національний університет імені Лесі Українки, 2016)
У гострих дослідах на щурах-самках із канюльованою жовчною протокою, які перебували під тіопента-ловим наркозом (5 мг/100 г), досліджено вплив тамоксифену (57,2 мкг/100 г) при його одноразовому внутріш-ньопортальному введенні на жовчносекреторну функцію печінки. За допомогою тонкошарової хроматографії визначено концентрацію жовчних кислот (вільних і кон’югованих із таурином і гліцином) в отриманих впродовж гострих дослідів п’яти півгодинних пробах жовчі. Influence of tamoxifen (57,2 mkg per 100 g of body weight) on secretion of bile and bile acids was studied in acute experiments in female rats. The concentration of bile acids (taurocholic acid, taurochenodeoxycholic and taurodeoxycholic acids, glycocholic acid, glycochenodeoxycholic and glycodeoxycholic acids, cholic acid, chenodeoxycholic and deoxycholic acids) were determine in six samples of bile using thin layer chromatography. Tamoxifen effects on nuclear estrogen receptors. Concentration decreasing of glycocholic acid (27,8–34,3 %, р < 0,01) and cholic acid were observed in female rats bile while such of taurocholic acid increased (16,8–30,7 % (р<0,05). Tamoxifen caused significant changes in the biotransformation and biosynthesis of bile acids in the liver of the experimental female animals, as reflected by changes in the ratio of trihydroxycholic and dihydroxycholic acids. Thus, tamoxifen influencing metabolism and transport of bile acids does not increase its lithogenic characteristics.
Bile Secretion Liver Function in the Female Rats at Estrogen Receptor Tamoxifen Blockade Conditions
Keywords: жовч; тамоксифен; естрогенові рецептори; печінка; жовчні кислоти; bile; tamoxifen; estrogen receptors; liver; bile acids